A three competing species model for wastewater treatment: case study on Taman Timur oxidation pond, Johor Bahru - Hamzah, A. S. A. (Penerbit UTM Press, 2016)
Oxidation pond techniques have practically proved to be effective for wastewater treatment process (WWTP) because of their low construction and operating cost. Cumbersome sampling is required to monitor the dynamics of the WWTP which also involves enormous costly work. Deterministic model accommodating the correlation between the amount of phototrophic bacteria in a product called mPHO (bioproduct used to improve water quality) and pollutant (bacteria E.coli and Coliform) existing in oxidation pond is developed to facilitate the analysis of this process. This study presents ordinary differential equation model for an oxidation pond to investigate the effect of mPHO on the degradation of pollutant. The model consists of a system of ordinary differential equations (ODE) with coupled reaction equations for the pollutant and phototrophic bacteria. The parameters of the model is estimated using the real data collected from an aerobic oxidation pond located in Taman Timor, Johor, Malaysia to illustrate a real life application of this model. The simulation results provide a better understanding of the ecological system in the oxidation pond.